PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN SKINTIFIC DI PLATFORM SHOPEE (Studi Kasus Pada Mahasiswi Manajemen Fakultas Ekonomi dan Bisnis UMB Angkatan 2020-2022) - Arora, Jessyca; Sri Ekowati (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to determine the influence of the marketing mix on creative purchasing decisions on the Shopee platform (Case study of management students at the UMB Faculty of Economics and Business Class 2020-2022). The objects of this research were management students from the UMB Faculty of Economics and Business Class 2020-2022 who were 71 creative consumers on the Shopee platform. The data analysis techniques used in this research used instrument tests, classical assumption tests, analysis of respondent responses, multiple linear regression analysis, hypothesis testing and analysis of the coefficient of determination (R2). The research results show that the product variable has a positive and significant effect on creative consumer purchasing decisions on the Shopee platform. The price variable also has a positive and significant influence on creative consumer purchasing decisions on the Shopee platform. Then the promotion variable shows a positive and significant influence on creative consumer purchasing decisions on the Shopee platform. The place variable shows a positive and significant influence on creative purchasing decisions on the Shopee platform. So, from the results of the research that has been carried out, it can be concluded that the marketing mix (product, price, promotion and place) has a partial and simultaneous influence on creative consumer purchasing decisions on the Shopee platform.